Feasibility and utility of the days of antibiotic spectrum coverage (DASC) in national antimicrobial use surveillance in Japan - Ichiro Kawamura; Sanae Suzuki; Mio Endo; Masaaki Ogawa; Satoshi Hasegawa (Antimicrobial Stewardship & Healthcare Epidemiology)
Abstract